Efektivitas Aturan Penggunaan Produk dalam Negeri pada Pengadaan Barang/Jasa Pemerintah - Wawan Zulmawan (LPPM Universitas Ekasakti Padang, 2023)
Various regulations for the use of Domestic Products have existed since 2014, but implementation in the procurement of goods/services has not run optimally, at least until the end of 2022. Through empirical normative legal research, a study was conducted on the rules for using the Domestic Product. Referring to Lawrence M. Friedman's theory of legal effectiveness, it is known that the cause of the ineffectiveness of this rules is due to the low understanding of legal substance due to the lack of socialization of the rules, the legal structure in the form of P3DN Teams that have not been formed in many government agencies, and the legal culture is still seen as a culture of apathy due to a lack of understanding of the rules. Therefore, in addition to imposing strict sanctions, the existence of Presidential Instruction number 2 of 2022 concerning Accelerating the Increase in the Use of Domestic Products and Products of Micro, Small Enterprises and Cooperatives in the Context of Succeeding the Proud Made in Indonesia National Movement in the Implementation of Government Goods/Services Procurement on the 30th March 2022, is expected to force the use of Domestic Products in procuring goods/services in government.